2022
DOI: 10.12680/balneo.2022.500
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tabata and HIIT Programs Regarding Body Composition and Endurance Performance among Female Handball Players

Abstract: Background: The purpose of the study was to analyze the effect of two different training modes towards the development of body composition, aerobic and anaerobic endurance of female handball players aged 18-23, in COVID-19 pandemic. (2) Methods: 18 female handball players from the second division were divided into two groups: Group 1 subject-ed to Tabata Program (n=9) and Group 2 trained using HIIT Program (n=9). (3) Results: Paired Sample T-Test was carried in the statistical analysis and the significance lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…In the randomized controlled trials, except the studies by Buchheit et al [11,12] and Mikalonytė et al [37], there was a significant inter-group benefit favorable to the HIIT intervention groups compared to the control groups. All 4 studies [16,30,31,52] with only experimental groups recorded positive effects in both interventions, and the two quasi-experimental studies [19,29] also recorded improvements.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the randomized controlled trials, except the studies by Buchheit et al [11,12] and Mikalonytė et al [37], there was a significant inter-group benefit favorable to the HIIT intervention groups compared to the control groups. All 4 studies [16,30,31,52] with only experimental groups recorded positive effects in both interventions, and the two quasi-experimental studies [19,29] also recorded improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Table 6 provides an assessment of the risk of bias for the non-randomized studies using the ROBINS-I instrument. Two [12,16] of the three studies presented an overall moderate risk of bias, due to deviations from intended interventions, while the study by Jurišic et al [31] had an overall low risk of bias, with low risk in all fields.…”
Section: Study Risk Of Bias Assessmentmentioning
confidence: 91%
See 1 more Smart Citation
“…This evolution in training methodologies has the potential to significantly impact the development of young athletes, preparing them more effectively for the demands of competitive sports [53][54][55][56][57]. In accordance with the trends of modernization and technology of sports training, we consider that in order to identify the theoretical and practical methodological aspects, an interdisciplinary approach is necessary in order to improve sports performances [58][59][60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that a level of motor ability development, especially coordination, directly and significantly influences the performance level of basketball players, particularly in the junior categories [ 16 , 17 , 18 ]. The effectiveness of a basketball player in the training process and during matches depends on the level of physical, technical, and tactical preparation in relation to the trends of dynamizing the game and the modernizing of specific training methodologies [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%